Opisthobranchs from American Atlantic warm waters - Marcus, E.; Marcus, E. (Bulletin of Marine Science of the Gulf and Caribbean, 1960)
In the winter of 1958/1959 Dr. Diva Diniz Corrêa, fellow of the Guggenheim Foundation, collected 25 opisthobranch species and one prosobranch (Lamellaria) in the Miami area. Of these 72 per cent are known from the coast of São Paulo, Brazil; hence Hedgpeth's inclusion (1957) of Southeast and South Florida in the same littoral province as Brazil is confirmed by the opisthobranchs. Of the 5 new species one is allied to boreal Atlantic and Pacific species, testifying to the Tertiary Caribbean-Pacific sea connection, and another belongs to a genus known only from the Indo-Westpacific. Of the Miami-São Paulo opisthobranchs, 11 per cent have a transatlantic distribution explainable by the much narrower ocean in the Tertiary. As the opisthobranch fauna of Miami is so similar to that of São Paulo, four species from Brazil were added, one of which (Rhizorus persimilis) was already known from Florida. The anatomy of this radulaless species is described for the first time.
CLEMAM P0877